RELASI MAKNA ULAMA DAN UMARA DALAM TAFSIR AL-AZHAR DAN TAFSIR KEMENAG RI - Jauhari Parma Susanto (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
This study discusses the semantic relationship between ulama (Islamic scholars) and umara (leaders) in the Qur'an, as explained in Tafsir al-Azhar and the Ministry of Religious Affairs' interpretation. Using a qualitative method with a library research approach and a thematic figure study approach, the findings indicate that ulama and umara are two inseparable entities. Both play vital roles in society, whether in religious or social contexts. The unity of ulama and umara is essential for building a nation that aspires to be a baldatun tayyibatun wa rabbun ghafur (a good and prosperous land under the forgiveness of Allah).